2024
DOI: 10.1002/adfm.202401011
|View full text |Cite
|
Sign up to set email alerts
|

Mott–Schottky Barrier Enabling High‐Performance Hydrazine‐Assisted Hydrogen Generation at Ampere‐Level Current Densities

Yaping Huang,
Xia Zhang,
Linfeng Li
et al.

Abstract: Local electron density manipulation can optimize the adsorption and desorption nature of catalysts leading to enhanced catalytic activity for water oxidation. Construction a Mott–Schottky barrier allows the electron transition in catalysts because of their different Fermi levels. Herein, a Pt@NiFc‐MOF Mott–Schottky heterojunction is constructed, in which electrons are transferred from NiFc‐MOF to Pt as triggered by the formed built‐in electric field at the interface. The as‐prepared Pt@NiFc‐MOF reveals excepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 74 publications
0
0
0
Order By: Relevance
“…Therefore, a series of MOFs have been employed to accelerate the dehydrogenation step of HzOR offering excellent performance. [82][83][84] Xi et al introduced a novel strategy involving metal node engineering to enhance the catalytic efficiency and stability of MOFs. 85 This involved the partial substitution of nickel with rhodium within Ni-BDC, resulting in the creation of an optimized catalyst termed NiRh 0.016 -BDC.…”
Section: (I) Hydrazine Oxidation Reaction (Hzor) With Mofsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, a series of MOFs have been employed to accelerate the dehydrogenation step of HzOR offering excellent performance. [82][83][84] Xi et al introduced a novel strategy involving metal node engineering to enhance the catalytic efficiency and stability of MOFs. 85 This involved the partial substitution of nickel with rhodium within Ni-BDC, resulting in the creation of an optimized catalyst termed NiRh 0.016 -BDC.…”
Section: (I) Hydrazine Oxidation Reaction (Hzor) With Mofsmentioning
confidence: 99%
“…88 Huang et al conducted a fascinating study where they integrated platinum (Pt) with NiFc-MOF to create a Mott-Schottky heterojunction. 84 Their research revealed electron transfer from NiFc-MOF to Pt, facilitated by the built-in electric field at the interface. The resulting Pt@NiFc-MOF catalyst exhibited impressive performance in an N 2 H 4 /H 2 O 2 fuel cell, achieving a maximum power density of 415.2 mW cm À2 at 80 1C, with exceptional stability demonstrated for 190 hours of operation at 500 mA cm À2 (measured at 25 1C).…”
Section: (I) Hydrazine Oxidation Reaction (Hzor) With Mofsmentioning
confidence: 99%
See 3 more Smart Citations